The Development of Scientific Hybrid Learning Model by Using the BRILIAN Application for the Science Field - Hariadi, Bambang; Sunarto, M.J. Dewiyani (Indonesian Research Journal in Education |IRJE|, 2023)
Scientific learning is a learning process that leads students to a science-based learning experience. Scientific learning implements specific methods for students to discover concepts and theories. This research was intended to develop a hybrid learning model which can be implemented for scientific learning. This was a research and development which aimed to develop a suitable learning model to be implemented in Moodle-based LMS named Brilian. Scientific Hybrid Learning (SHL) model tests were conducted in terms of validity and practicality. The results showed (1) that the score for the content validity test on average was 3.71 statistic rÎ± = 0.25 and Î± = 0.81, the construct validity score on average was 3.82 statistic rÎ± = 0.20 and Î± = 0.75. (2). The practical validity test score on average was 3.63 statistic rÎ± = 0.91 and Î± = 0.99. The conclusion is that the SHL model is qualified in terms of the validity of contents and constructs and practicality for students. The research implied that a good SHL model can be implemented to increase students learning outcomes based on science. The continuation of this research can focus on monitoring the SHL model's effectiveness in improving students' learning outcomes on science-based subjects.